A case‐control evaluation of fungiform papillae density in burning mouth syndrome. (22nd August 2017) - Naud, Jason M.; Benca, Laura; Drangsholt, Mark T.; LeResche, Linda; Coldwell, Susan E.
Abstract : Hypothesis: It has been hypothesized that high fungiform papillae density may be a risk factor for developing the taste and pain alterations characteristic of burning mouth syndrome. Objective: Evaluate whether fungiform papillae density, taste sensitivity, and mechanical pain sensitivity differ between burning mouth syndrome cases and controls. Study Design: This case‐control study compared cases diagnosed with primary burning mouth syndrome with pain‐free controls. Methods: Participants (17 female cases and 23 female controls) rated the intensity of sucrose, sodium chloride, citric acid, and quinine applied separately to each side of the anterior tongue and sampled whole mouth. Mechanical pain sensitivity was assessed separately for each side of the tongue using weighted pins. Digital photographs of participants' tongues were used to count fungiform papillae. Results: Burning mouth syndrome cases had increased whole mouth taste intensity. Cases also had increased sensitivity to quinine on the anterior tongue, as well as increased mechanical pain sensitivity on the anterior tongue. Fungiform papillae density did not differ significantly between cases and controls. Fungiform papillae density on the left and right sides of the tongue were correlated in controls; however, there was no left/right side correlation in cases. Conclusion: Cases had increased pain and taste perception on the anterior tongue. The lack of correlation between left and right fungiform papillae density in cases may be an indication of asymmetrical lingual innervation in these patients. Level of Evidence: 3b. Laryngoscope, 128:841–846, 2018